Double autoinhibition mechanism of signal transduction ATPases with numerous domains (STAND) with a tetratricopeptide repeat sensor - Lisa, María Natalia (2019)
Upon triggering by their inducer, signal transduction ATPases with numerous domains (STANDs), initially in monomeric resting forms, multimerize into large hubs that activate target macromolecules. This process requires conversion of the STAND conserved core (the NOD) from a closed form encasing an ADP molecule to an ATP-bound open form prone to multimerize. In the absence of inducer, autoinhibitory interactions maintain the NOD closed. In particular, in resting STAND proteins with an LRRor WD40-type sensor domain, the latter establishes interactions with the NOD that are disrupted in the multimerization-competent forms. Here, we solved the first crystal structure of a STAND with a tetratricopeptide repeat sensor domain, PH0952 from Pyrococcus horikoshii, revealing analogous NOD-sensor contacts. We use this structural information to experimentally demonstrate that similar interactions also exist in a PH0952 homolog, the MalT STAND archetype, and actually contribute to the MalT autoinhibition in vitro and in vivo. We propose that STAND activation occurs by stepwise release of autoinhibitory contacts coupled to the unmasking of inducer-binding determinants. The MalT example suggests that STAND weak autoinhibitory interactions could assist the binding of inhibitory proteins by placing in register inhibitor recognition elements born by two domains.